RF-INDUCED TEMPERATURE INCREASE IN A STRATIFIED MODEL OF THE SKIN FOR PLANE-WAVE EXPOSURE AT 6–100 GHZ - Christ, Andreas; Samaras, Theodoros; Neufeld, Esra; Kuster, Niels (Radiation protection dosimetry, 2020)
Abstract This study assesses the maximum temperature increase induced by exposure to electromagnetic fields between 6 and 100 GHz using a stratified model of the skin with four or five layers under plane wave incidence. The skin model distinguishes the stratum corneum (SC) and the viable epidermis as the outermost layers of the skin. The analysis identifies the tissue layer structures that minimize reflection and maximize the temperature increase induced by the electromagnetic field. The maximum observed temperature increase is 0.4°C for exposure at the present power density limit for the general population of 10 W m −2 . This result is more than twice as high as the findings reported in a previous study. The reasons for this difference are identified as impedance matching effects in the SC and less conservative thermal parameters. Modeling the skin as homogeneous dermis tissue can underestimate the induced temperature increase by more than a factor of three.